Geology, alteration, and mineralization of the El Alacran area, northern Sonora, Mexico - Dean, Darrel Allen, 1943- (The University of Arizona., 1975)
El Alacran, northern Sonora, Mexico, is a high-level, Laramide porphyry copper deposit encompassing an east-west elongated altered and mineralized area of 2.7 by 6 km. A small quartz latite porphyry plug forcefully intrudes comagmatic(?) Late Cretaceous or Early Tertiary andesitic to quartz latite volcaniclastic rocks.Veinlet-controlled and pervasive potassic, Type I phyllic, and transition type alteration with related base-metal mineralization postdates pervasive propylitic alteration and is related in space and time to the intrusive and its associated intrusion-breccia annulus. Potassic alteration is dated by K-Ar at 55.4 +- 1.2 m.y. Later pervasive and veinlet-controlled Type II phyllic and minor advanced argillic alteration is associated with intrusive breccia dikes and pipes which are genetically related to degassing of the system. Minor veinlet-controlled late-stage alteration followed. Hypogene zoning is exhibited by alteration, mineralization, total sulfide volume, mineralized fracture density, and geochemistry with zoning being centered over or to the east of the exposed intrusive. Supergene enrichment processes have modified hypogene sulfides, oxides, and silicates and have formed a copper enriched blanket which underlies a leached cap. The blanket is characterized by a chalcocite zone which grades downward into a bornite-digenite-covellite zone and then into low-grade protore. Although the enriched blanket appears to be subeconomic, this study indicates potential for a deep, high-grade protore zone.